Effects of parental mental health and family environment on impulsivity in preadolescents: a longitudinal ABCD study® - Gebru, Nioud Mulugeta; Goncalves, Priscila Dib; Cruz, Rick A.; Thompson, Wesley K.; Allegair, Nicholas; Potter, Alexandra; Garavan, Hugh; Dumas, Julie; Leeman, Robert F.; Johnson, Micah (Frontiers in Behavioral Neuroscience, 2023)
Introduction: Impulsivity is a known risk factor for the development of substance use disorders and other psychiatric conditions that is influenced by both genetics and environment. Although research has linked parental mental health to children’s impulsivity, potential mediators of this relationship remain understudied. The current investigation leverages the large national Adolescent Brain Cognitive Development (ABCD) Study to assess the mediating role of family conflict – an important social context for youth development – in the relationship between parental mental health and youth impulsivity. Methods: Data were from the first three annual waves of the ABCD study (Baseline N=11,876 children, Mage=9.9 years; 48% female; 52% White). Parental mental health conditions were self-reported internalizing, externalizing, and total problems. Youth completed the family conflict scale, and Urgency, Planning (lack of), Perseverance (lack of), Sensation Seeking, and Positive Urgency (UPPS-P) scale to measure impulsivity. To determine if within-family change in conflict from baseline to year 1 explained changes in the strength of relations between baseline parental mental health and year 2 youth impulsivity, longitudinal causal mediation analyses were conducted, controlling for demographic factors (i.e., age, sex, race, household income, parental education, marital status), as well as baseline levels of family conflict and outcomes. Separate mediation models were run for each mental health condition and each UPPS-P subscale. Results: Above and beyond bivariate relations, longitudinal mediation models, which included covariates, showed family conflict significantly (ps < .001) mediated relations between all three parental mental health conditions and all but one (i.e., sensation seeking) UPPS-P subscales. The proportion mediated through family conflict for internalizing problems and total problems on facets of impulsivity (except sensation seeking) ranged from 9% (for lack of perseverance) to 17% (for lack of planning). Proportion mediated via family conflict for externalizing problems on youth’s impulsivity (except sensation seeking) was slightly higher, ranging between 13% (lack of perseverance) to 21% (lack of planning). Discussion: Family conflict may be an important intergenerational factor linking parental mental health and youth’s impulsivity. Addressing parental mental health and family conflict may help curb increased impulsivity in youth, and in turn reduce adolescent substance use disorders.